Pengaruh Kepemilikan Institusional, Leverage, Dan Faktor Lainnya Terhadap Manajemen Laba - Rahmawati, Fitri; Indrastuti, Dewi Kurnia (Media Bisnis, 2024)
This research aims to obtain empirical evidence about the effect of independent variables on the dependent variable and analyse factors that affecting earnings management. The independent variables in this research are institutional ownership, leverage, firm size, dividend policy, independent commissioner, and audit quality. This research used sample of 153 data from 51 manufacturing companies in the non cyclicals, cyclicals, and basic materials sector listed on the Indonesia Stock Exchange for the priode 2020 to 2022. This study used purposive sampling method for sample selection and used multiple regression for data analysis. The empirical evidence obtained from this study shows that independent commissioners and audit quality have a negative effect on earnings management. These results indicate that the presence of Independent commissioners will enhance the quality of supervision over manager behavior so that earnings management practices will decrease. Earnings management is negatively impacted by audit quality because managers are less likely to use earnings management techniques when an audit is conducted by an auditor with high capability, competence, independence, and experience. Further, institutional ownership, leverage, firm size, dividend policy have no effect on earnings management.